Identifying the prevalence and correlates of multimorbidity in middle-aged men and women: a cross-sectional populationbased study in four African countries - Lisa K Micklesfield; Richard Munthali; Godfred Agongo; Gershim Asiki; Palwende Boua; Solomon SR Choma; Nigel J Crowther; June Fabian; Francesc Xavier Gómez-Olivé; Chodziwadziwa Kabudula; Eric Maimela; Shukri F Mohamed; et al. (My University, 2023)
Objectives To determine the prevalence of multimorbidity, to identify which chronic conditions cluster together and to identify factors associated with a greater risk for multimorbidity in sub-Saharan Africa (SSA). Design Cross-sectional, multicentre, population-based study. Setting Six urban and rural communities in four subSaharan African countries. Participants Men (n=4808) and women (n=5892) between the ages of 40 and 60 years from the AWI-Gen study. Measures Sociodemographic and anthropometric data, and multimorbidity as defined by the presence of two or more of the following conditions: HIV infection, cardiovascular disease, chronic kidney disease, asthma, diabetes, dyslipidaemia, hypertension. Results Multimorbidity prevalence was higher in women compared with men (47.2% vs 35%), and higher in South African men and women compared with their East and West African counterparts. The most common disease combination at all sites was dyslipidaemia and hypertension, with this combination being more prevalent in South African women than any single disease (25% vs 21.6%). Age and body mass index were associated with a higher risk of multimorbidity in men and women; however, lifestyle correlates such as smoking and physical activity were different between the sexes. Conclusions The high prevalence of multimorbidity in middle-aged adults in SSA is of concern, with women currently at higher risk. This prevalence is expected to increase in men, as well as in the East and West African region with the ongoing epidemiological transition. Identifying common disease clusters and correlates of multimorbidity is critical to providing effective interventions.